Phospholipidase Dδ Negatively Regulates the Function of Resistance to Pseudomonas syringae pv. Maculicola 1 (RPM1) - Yuan, Xin; Wang, Zhangying; Huang, Jianzhong; Xuan, Hua; Gao, Zhiyong (Frontiers in Plant Science, 2019)
RPM1 is a plant immune receptor that specially recognizes pathogen-released effectors to activate effector-triggered immunity (ETI) in Arabidopsis thaliana. RPM1 triggers ETI and hypersensitive response (HR) for disease resistance. Previous reports indicated that Phospholipase D (PLD) positively regulated RPM1-mediated HR. However, single, double, and triple pld knock-out mutants of 12 members of the PLD family in A. thaliana did not show suppressed RPM1-mediated HR, indicating the functional redundancy among PLD members. In this study, we revealed that PLD could negatively regulate the function of RPM1. We found that RPM1 interacted with PLDδ, but did not interact with PLDβ1, PLDβ2, and PLDγ3. Overexpression of PLDδ conducted to a reduction of protein level and corresponding activity of RPM1. We found that abscisic acid (ABA) reduced the protein level of RPM1, and the ABA-induced RPM1 reduction required PLD activity and PLD-derived phosphatidic acid (PA). Our study shows that PLD plays both negative and positive roles regulating the protein level and activity of RPM1 during stress responses in plants. PLD proteins are regulating points to integrate the abiotic and biotic responses of plants.